Métodos de aprendizaje y su influencia en niños con TDAH, del 3er año de EGB de la U.E Juan E Verdesoto - Prado Tirape, Emely Eduvyd (2023)
The purpose of this case study is to explore how learning methods influence children with ADHD in their third year of basic education at the Juan E. Verdesoto Educational Unit. In essence, this study highlights the importance of addressing the educational needs of these students in an individualized manner. The adaptation of pedagogical strategies to the particularities of ADHD, can play a crucial role in mitigating the difficulties they face in areas such as concentration, organization and planning, which, in turn, can boost a more consistent academic performance in various disciplines. The relevance of this study lies in its ability to shed light on how educational approaches impact children with ADHD, and how this understanding can foster the creation of a more inclusive and high-quality educational system, not only at the Juan E. Verdesoto Educational Unit, but nationally. Inclusive strategies, such as the personalization of learning plans, prove to be essential elements in helping these children reach their full potential. Flexibility in the implementation of these strategies is a key component, as plans must evolve as students’ progress. In summary, this study establishes a solid foundation for effectively addressing the challenges presented by ADHD in the educational context, simultaneously advancing inclusion and equity. Tailoring teaching strategies to the individual needs of students with ADHD can improve the path to overcoming the barriers they face and allow them to flourish in their educational process.